The sexual and reproductive health care market in Bangladesh: where do poor women go? - Rashid, Sabina Faiz; Akram, Owasim; Standing, Hilary (© 2011 Reproductive Health Matters., 2017)
This article was published in the Reproductive Health Matters [ © 2011 Reproductive Health Matters. ] and the definite version is available at : http://dx.doi.org/10.1016/S0968-8080(11)37551-9 The Journal's website is at: http://www.rhm-elsevier.com/article/S0968-8080(11)37551-9/abstract